Factors that Cause the Intention to Continue Using the Traveloka Mobile Application - Santoso, Hendra Gilbiyanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to examine the factors that influence the intention of continued to use the Traveloka Mobile Application. The theory used is a theoretical model adapted from Lee, (2018). The data used in this study are primary data obtained from distributing questionnaires. Respondents in this study were 237 respondents who had used and made transactions on the Traveloka application for the last 3 months. The sampling technique of this research is non-probability sampling. This study uses a quantitative approach through statistical testing. The analysis in this study uses the Structural Equation Modeling (SEM) model and is processed using SPSS 20 and AMOS 20 software to test the measurement model and structural model. The results of this study are Argument Quality has a positive effect on Perceived Ease to Use, Usefulness and Parasocial Interaction. Perceived Ease to Use has a positive effect on Usefulness, and Usefulness has a positive effect on Continued to Use Mobile Apps Intention. Source Credibility has no effect on Usefulness and Parasocial Interaction, Parasocial Interaction has no effect on Continued to Use Mobile Apps Intention.